Determination of Ion-Pair Formation Constants for MA+ Ions (M = Ca, Sr, Ba, Cu, Cd) with A- = Picrate Ion in Water by Picric Acid Extraction into Benzene - Kudo, Yoshihiro; Nakajima, Shinichi; Horiuchi, Naoki (Journal of Applied Solution Chemistry and Modeling, 2016)
Ion-pair formation constants (KMA0) for MA+ = MPic+ and MCl+ in water were determined at 298 K and ionic strength â†’ 0 by extraction experiments of picric acid (HPic) in the presence of M(II) in the water phase into benzene (Bz) and by potentiometry with a commercial Cl--selective electrode, respectively. Here, M denotes Ca(II), Sr(II), Ba(II), Cu(II), and Cd(II). In adding Pb(II) data, a relation between KMA0 values was KMCl0<KMPic0 for a given M(II).For CdPic+, the KMA0 value (= 136mol-1 dm3) determined by the HPic extraction was somewhat larger than that (= 108) potentiometrically-determined before with a Cd2+-selective electrode, while for CaPic+ the former value (= 89) equaled the latter one (= 88) determined before with a Ca2+-selective electrode.